2019
DOI: 10.1002/eat.23085
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy eating and weight dissatisfaction in adolescents who never, occasionally, or regularly use smokeless tobacco (Swedish snus)

Abstract: Objective: Although cigarette smoking has been linked to weight-related concerns and unhealthy weight control practices, little is known about weight dissatisfaction and eating among adolescents who use smokeless tobacco (SLT) products. The use of Swedish moist snuff (snus) has increased dramatically over recent years, surpassing cigarette smoking among young people in several countries. This study investigated differences in unhealthy eating behaviors and weight dissatisfaction in male and female adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In support, studies confirmed that the desire to be thin and control weight was positively associated with increased cigarette smoking in adolescents, particularly among girls (Kendzor et al, 2007). Moreover, a study conducted on Swedish adolescents, aged 16-19 years, reported the association between increased snus use and unhealthy eating behaviours (Reas et al, 2019). Specifically, in both genders, meal skipping was more frequent among adolescents that use snus, while girls using snus had two to three times higher odds of skipping breakfast, lunch and dinner.…”
Section: Dietary Habits and Alcohol And Tobacco Consumptionmentioning
confidence: 70%
See 1 more Smart Citation
“…In support, studies confirmed that the desire to be thin and control weight was positively associated with increased cigarette smoking in adolescents, particularly among girls (Kendzor et al, 2007). Moreover, a study conducted on Swedish adolescents, aged 16-19 years, reported the association between increased snus use and unhealthy eating behaviours (Reas et al, 2019). Specifically, in both genders, meal skipping was more frequent among adolescents that use snus, while girls using snus had two to three times higher odds of skipping breakfast, lunch and dinner.…”
Section: Dietary Habits and Alcohol And Tobacco Consumptionmentioning
confidence: 70%
“…Specifically, in both genders, meal skipping was more frequent among adolescents that use snus, while girls using snus had two to three times higher odds of skipping breakfast, lunch and dinner. Importantly, girls who used snus perceived themselves as overweight; thus, they probably used snus to decrease their weight and form better body shape (Reas et al, 2019). Even the studies in aesthetic sports confirmed such findings, where authors repeatedly reported smoking in female professionals who strive to maintain their body weight at a low level (i.e.…”
Section: Dietary Habits and Alcohol And Tobacco Consumptionmentioning
confidence: 97%
“…In a previous Swedish study (9,954 participants, including 839 exclusive snus users), it was reported that snus users were less likely to be daily consumers of fruit and berries than non-tobacco users (21). In that study, as well as in a previous Norwegian study (23,622 participants, including 4,918 occasional or daily snus users) (20), snus users also had less regular eating habits than non-tobacco users.…”
mentioning
confidence: 73%
“…Interestingly enough, the dietary habits of snus users have seldom been studied. One Norwegian study found that snus users were less likely to have regular eating habits than their non-using peers ( 20 ), and a Swedish study found that snus users were less likely to have regular breakfast habits and to be daily consumers of fruit and berries compared with non-tobacco users ( 21 ). In contrast, it is well-established that cigarette smokers have unhealthier diets than non-tobacco users with respect to both macronutrients (exemplified by, among others, higher intakes of total and saturated fat and lower intakes of polyunsaturated fat and fiber) ( 22 ) and overall diet quality (exemplified by a higher dietary energy density [energy per gram of food]) ( 23 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%